Penegakan Hukum Tindak Pidana Desersi terhadap Anggota TNI di Pengadilan Militer III-12 Surabaya (International Forum of Researchers and Lecturers, 2024)
The purpose of the author's research is to explain how the law enforcement process of desertion crime against TNI members in Military Court III-12 Surabaya. Desertion is act of a military person who leaves his duties and responsibilities without official permission. Which is against the law. This research was conducted using empirical juridical method with the main topic of discussion, namely measuring the effectiveness of law enforcement desertion crimes in Military Court III-12 Surabaya and the results of this study indicate the process of law enforcement desertion crimes in Military Court III-12 Surabaya has been carried out in accordance with applicable legislation starting from the administrative stage to the reading of the verdict.